2004
DOI: 10.1002/hep.20086
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte proliferation and tissue remodeling is impaired after liver injury in oncostatin M receptor knockout mice

Abstract: Oncostatin M (OSM) is a member of the IL-6 family of cytokines. Mice deficient in the OSM receptor (OSMR -/-) showed impaired liver regeneration with persistent parenchymal necrosis after carbon tetrachloride (CCl 4 ) exposure. The recovery of liver mass from partial hepatectomy was also significantly delayed in OSMR -/-mice. In contrast to wildtype mice, CCl 4 administration only marginally induced expression of tissue inhibitor of metalloproteinase (TIMP)-1 and TIMP-2 genes in OSMR -/-mice, correlating with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
119
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 51 publications
5
119
1
Order By: Relevance
“…It is likely that the infiltrating macrophages or neutrophils secrete OSM that in turn functions to recruit additional inflammatory cells into the injured muscles and to prevent premature differentiation of myoblasts [32]. In addition to a direct effect on myoblasts shown in this report, OSM may also contribute to muscle regeneration by regulating muscle stem cell niche, as OSM/ OSMR is known to regulate the expression of matrix metalloproteinases and tissue inhibitors of metalloproteinases [69][70][71]. The balanced action of these two classes of proteins regulates the integrity of extracellular matrix and is essential during tissue remodeling and repair.…”
Section: The Role Of Osm In the Early Phase Of The Injury-induced Musmentioning
confidence: 68%
“…It is likely that the infiltrating macrophages or neutrophils secrete OSM that in turn functions to recruit additional inflammatory cells into the injured muscles and to prevent premature differentiation of myoblasts [32]. In addition to a direct effect on myoblasts shown in this report, OSM may also contribute to muscle regeneration by regulating muscle stem cell niche, as OSM/ OSMR is known to regulate the expression of matrix metalloproteinases and tissue inhibitors of metalloproteinases [69][70][71]. The balanced action of these two classes of proteins regulates the integrity of extracellular matrix and is essential during tissue remodeling and repair.…”
Section: The Role Of Osm In the Early Phase Of The Injury-induced Musmentioning
confidence: 68%
“…The first goal of this study was to establish the signaling specificity of IL-31 and OSM, two cytokines predicted to be relevant for regulating epithelial cells (8,15,22,23,35). Assessment of signaling specificity was in part prompted by the prediction that the receptors for these two cytokines, like the other members of the IL-6 cytokine receptors, exert redundant functions due to shared receptor subunits (25).…”
Section: Discussionmentioning
confidence: 99%
“…They have also shown that the administration of OSM reduces CCl 4 -induced acute liver failure in wildtype mice. 21 These results suggest that OSM, like HGF, plays an important role in liver regeneration.Recently, we have succeeded in isolating rat OSM cDNA. 22 In this study, we examined whether the introduction of this OSM cDNA enhances liver regeneration and suppresses fibrogenesis in rats administrated with dimethylnitrosamine (DMN).…”
mentioning
confidence: 84%
“…They have also shown that the administration of OSM reduces CCl 4 -induced acute liver failure in wildtype mice. 21 These results suggest that OSM, like HGF, plays an important role in liver regeneration.…”
mentioning
confidence: 84%